(untitled) (Jurnal TEKNODIK, 2015)
Abstrak: Pemanfaatan tablet (e-Sabak) untuk pembelajaran di Indonesia dirintis oleh Pemerintah melalui Kementerian Pendidikan dan Kebudayaan sejak tahun 2011. Namun demikian, kebijakan ini baru direalisasikan pada tahun 2015. Pemanfaatan e-Sabak difokuskan pada pembelajaran di Sekolah Dasar khususnya di daerah terpencil, tertinggal, dan terdepan (3T). Pembahasan tentang penggunaan tablet untuk pembelajaran di Indonesia masih terbatas. Kajian ini ingin membahas: (1) manfaat e-Sabak untuk pembelajaran; (2) kesiapan anak Indonesia, khususnya siswa SD di daerah 3T, untuk menggunakan e-Sabak dalam pembelajaran; dan (3) persiapan sekolah dalam pemanfaatan e-Sabak untuk pembelajaran. Hasil kajian menyatakan bahwa tablet (e-Sabak) untuk pembelajaran dapat dimanfaatkan sebagai alat bantu pembelajaran, sumber pembelajaran, sarana interaksi pembelajaran, pengelolaan sistem pembelajaran, dan alat penilaian pembelajaran. Saat ini, tablet hanya akan digunakan sebagai sumber pembelajaran menggantikan buku. Anak Indonesia sudah siap untuk menggunakan e-Sabak dalam pembelajaran mereka. Kesiapan sekolah untuk melakukan pembelajaran dengan tablet perlu mendapatkan dukungan kebijakan yang konsisten dari pusat hingga sekolah, pelatihan guru dan siswa, penambahan infrastruktur (listrik, internet/intranet, LCD projector, komputer/laptop, dan lain sebagainya), serta penyiapan konten pembelajaran yang sesuai. Kata Kunci: Tablet (e-Sabak), belajar, pembelajaran di Indonesia Abstract: The use of e-Sabak for learning in Indonesia was initiated by the Government, through the Ministry of Education and Culture, in 2011. However, this policy has just been realized in 2015. The use of e-Sabak will be focused on learning in elementary schools, especially those located in remote, left, and forefront areas (3T). Studies on tablet usage (e-Sabak) for learning in Indonesia are still limited. This study tries to explore the following issues: (1) The benefis of e-Sabak for learning; (2) The readiness of Indonesian children, especially the students of elementary schools in remote, left, and forefront areas to use e-Sabak in their learning; and (3) the preparations that should be made by schools before utilizing e-Sabak for learning. The result of the study shows that e-Sabak can be used as a learning tool, a learning resource, a medium of learning interaction, a learning system management, and a learning evaluation tool. Currently, e-Sabak is only used as a learning resource replacing books. Indonesian children have been ready to utilize e-Sabak tablet for their learning. Schools’ readiness in utilizing e-Sabak in their teaching-learning process should be supported by relevant and consistent policies from the central government up to schools, teacher as well as student trainings, infrastructure provision (electricity, internet/intranet, LCD projectors, computers/laptops, and so on), and relevant learning content provisions. Key Words: Tablet (e-Sabak), learning, education in Indonesia